TEMPAT PENYIMPANAN PERLENGKAPAN PEMBUATAN PIN - Shyafary, Darius; Wahyuni, Merlinda (Indonesian Society of Applied Science, 2018)
abstractIn this modern era, most people need objects that are useful for their daily routine and as a means of communication that usually form of identification or souvenir. One of the most common identification and souvenirs used by the public is the pins and key chains. Pick-knitting materials and key chains that belong to many diverse sizes should have a special storage area that can be used in addition to storing pin fixtures, but also used to protect from damage and not scattered anywhere. However, from the observation of some printing media in Samarinda one of them in Mabes O2, it is known that the storage of pin equipment that they use today is only a plastic paper stacked in a cardboard box or plastic so that the equipment makes the pin making material becomes very easy to mix. In a report entitled